Sistem Pendukung Keputusan Pemilihan Tempat Nongkrong dengan Metode Analytical Hierarchy Process - Eka Martyani; Santoso (LPPM Universitas Adiwangsa Jambi, 2019)
Nowadays hangout can be found everywhere. Regardless of age or circles and anywhere. It is undeniable that as time goes by hangout will continue to grow according to market needs. Judging from the benefits of this hangout place is actually just a place to communicate whether chatting or chatting to friends and family. With a variety of hangouts in this era, business people can attract the attention of many people, especially the millennials. The number of hangouts at this time, making this study take a sample of four types of hangouts that are of interest to today's millennials and based on market share data in Indonesia, the decision shows that the highest priority weight is The Clave with a value of 0.335 or 33%. respondents tend to choose The Clave as the best Millennial Hangout in terms of menu, price, facilities and photogenic. Followed by D & C with a value of 0.286 or 29%, then Warung Upnormal with a value of 0.241 or 24% and the last is Es Bidadari with a value of 0.138 or 14%. This research was made using the Analytical Hierarchy Process (AHP) method. By using the AHP method, it is hoped that it can help the selection of hangouts that are in great demand by millennials and decent and affordable prices.